Istighotsah Sebagai Upaya Menumbuhkan Kecerdasan Spiritual Santri di Pondok Pesantren Putri Al-Mahrusiyah - Anisa Fitriati; Makhfud (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
This article reveals about the implementation and efforts to cultivate the spiritual intelligence of students through the practice of istighotsah. Istighotsah is practiced by Muslims as a medium to ask Allah for help from the dangers of the world that will plunge people into misleading paths and as human ta'aluq siroj to God. This research uses qualitative research with a phenomenological approach. The results reveal that the implementation of istighotsah is used as a medium of communication with the aim of asking for help from Allah, and submitting to Allah. In addition to getting closer to God, istighatsah also trains students to think positively, always be patient, istiqomah, and live life only expecting the pleasure of God. Thus, it will lead to behavior that leads to not getting the pleasure of God, such as immorality, too much love for material things, and so on.